Two-Stage Pricing Decision for Low-Carbon Products Based on Consumer Strategic Behaviour. (13th January 2021) - Che, Cheng; Zhang, Zhihong; Zhang, Xiaoguang; Chen, Yi
Abstract : The development of information technology has changed the pricing strategy of retailers, and consumers have also made strategic consumption behaviours accordingly. At the same time, changes in the environment have caused changes in the retailer's products and raised consumers' environmental awareness. This paper uses a two-stage pricing model to study the low-carbon product pricing decisions of retailers based on strategic consumers with low-carbon preferences in two situations. Through the analysis of low-carbon and ordinary products in two situations, the following conclusions can be drawn: (1) In a market where retailers only sell low-carbon products, product prices and profits increase as consumers' green preference θ increases. (2) In the low-carbon product and ordinary product markets, the price and profit of low-carbon products increase with regard to consumers' green preference θ . (3) In the second stage, when consumers' intertemporal discount factor β for ordinary products is larger than that of low-carbon products, the retailer's total profit is smaller. The research conclusion comprehensively analyses the impact of customer strategic behaviour on the two-stage pricing decision of green differentiated products, which provides a very important reference for retailers to make pricing optimization decisions.